การจัดสรรความเสี่ยงและการวิเคราะห์ความเสี่ยงของสัญญาจ้างออกแบบวิศวกรรม จัดหา และก่อสร้าง สำหรับโครงการโรงไฟฟ้า - เบญจพล พินิจการวัฒน์กุล (จุฬาลงกรณ์มหาวิทยาลัย, 2011)
Since the demand of electricity consumption in Thailand has been increasing continuously, constructing new power plants is unavoidable. Power plant projects are large, complex, and expensive construction works. The projects are always associated with various risk factors, some of which are different from those in conventional construction projects. Risk management is often used for planning and managing power plant project development. The objectives of this research are (1) to identify and analyze risk allocation in engineering, procurement, and construction (EPC) contracts of power plant projects to yield an appropriate risk allocation scheme; and (2) to analyze the significance level of risk factors and explore risk-response measures by contractors in power plant projects. Based on extensive literature reviews and in-depth interviews with 22 experienced participants from four power plant case study projects, 39 risk factors were identified and categorized into nine groups. By analyzing risk allocation of the EPC contracts in the case studies, it was found that the contracts address most of the risk factors, and most of them are allotted to the contractor. By considering several fundamental concepts of risk allocation, an appropriate risk allocation scheme was developed by allotting 24, 8, and 7 risk factors to the employer, the contractor, and both parties, respectively. The research also suggests 14 important issues for improving EPC contracts in power plant projects. To investigate the risk-response measures of contractors for the allocated risk factors, the significance level of each risk factor was assessed by six contractors that are experienced in power plant projects. Modified Delphi technique was introduced to collect relevant data. It was found that the most critical risk groups entail personnel, design, and operation. The risk-response measures for each risk factor were then explored. The measures that were most widely used by contractors were risk reduction, risk avoidance, and risk transfer, respectively. These results can be used as a guideline for preparing the power plant EPC contracts that address all important risk factors, which are unambiguously and appropriately allocated to the contracting parties. They also provide a procedure for assessing the significance level of risk factors and preparing risk-response measures for future power plant projects.